2016
DOI: 10.3354/aei00165
|View full text |Cite
|
Sign up to set email alerts
|

Area use and movement patterns of wild and escaped farmed Atlantic salmon before and during spawning in a large Norwegian river

Abstract: We compared the within-river movements and distribution of wild and escaped farmed Atlantic salmon Salmo salar before and during spawning in the Namsen river system of Central Norway. A total of 74 wild and 43 escaped farmed salmon were captured at sea, tagged with radio transmitters and released. Based on our examinations, most, if not all salmon (farmed and wild) entering the River Namsen were sexually mature. Farmed salmon entering the river system had a higher probability than wild individuals of reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Data from early surveys conducted in Norway revealed unweighted annual average maturation of escapes captured in rivers as 91.9% (range 77%–100% over the 12 years) and 86.8% (range 64%–100%) for males and females, respectively (Fiske et al., ). Also, in a recent study conducted in the River Namsen, middle Norway, most of the escapees entering the river were mature or maturing (Moe et al., ). In contrast, all of 29 small (0.4 kg) escapees captured in the River Steinsdalselva in western Norway in 2012 were immature (Madhun et al., ), and observations of large numbers of immature adults have been reported in rivers in Canada (Carr, Lacroix et al., ; Lacroix et al., ).…”
Section: Ecology Preceding Introgressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from early surveys conducted in Norway revealed unweighted annual average maturation of escapes captured in rivers as 91.9% (range 77%–100% over the 12 years) and 86.8% (range 64%–100%) for males and females, respectively (Fiske et al., ). Also, in a recent study conducted in the River Namsen, middle Norway, most of the escapees entering the river were mature or maturing (Moe et al., ). In contrast, all of 29 small (0.4 kg) escapees captured in the River Steinsdalselva in western Norway in 2012 were immature (Madhun et al., ), and observations of large numbers of immature adults have been reported in rivers in Canada (Carr, Lacroix et al., ; Lacroix et al., ).…”
Section: Ecology Preceding Introgressionmentioning
confidence: 99%
“…While farmed escapees may successfully spawn in the same areas of rivers as wild fish (Butler et al., ), studies have shown that adult farmed escapees do not necessarily use the same regions of a river during the spawning season as wild fish (Moe et al., ; Okland et al., ; Thorstad et al., ). Furthermore, in the absence of significant migration barriers such as large waterfalls, farmed escapees have a tendency to migrate to the upper reaches of rivers (Moe et al., ; Thorstad et al., ). In addition to area use differences, the timing of farmed salmon spawning may not be synchronized with the native population (Fleming et al., ; Moe et al., ; Saegrov et al., ; Webb et al., ).…”
Section: Ecology Preceding Introgressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitney et al 2016) of the recovery time of salmon after exercise. In general, longer buffer periods will be best but this must be considered against the run timing of farmed fish to ensure a representative sample (Moe et al 2016, Svenning et al 2017. Farmed salmon also tend to have a different distribution within the river than wild fish, and have been observed migrating farther upriver than wild fish (Moe et al 2016); therefore, efforts to refine surveillance fishing methods may be necessary to further ensure representative sampling.…”
Section: Discussionmentioning
confidence: 99%
“…However, farmed Atlantic salmon are known to enter rivers later in the season than wild fish (e.g. Moe et al 2016, Svenning et al 2017, and often after the recreational fishery has closed. Therefore, scale samples obtained during the summer underestimate the extent of farmed salmon in the population.…”
Section: Introductionmentioning
confidence: 99%